Pricing of payments - Malte Krüger (Research On Money in the Economy (ROME), 2009)
The pricing of payments has received increasing attention of regulators. In many cases, regulators are concerned that consumers do not face cost based prices. They argue that without cost based prices consumers will make inefficient choices. In this paper, it is argued that both, economics of scale and the particular laws governing pricing in two-sided markets provide a case against cost based pricing.
Keywords: L14; L41; E42; 330; Two-sided markets; interchange fees; surcharging; pricing strategies